Initiation of ART during early acute HIV infection preserves mucosal Th17 function and reverses HIV-related immune activation. - Alexandra Schuetz; Claire Deleage; Irini Sereti; Rungsun Rerknimitr; Nittaya Phanuphak; Yuwadee Phuang-Ngern; Jacob D Estes; Netanya G Sandler; Suchada Sukhumvittaya; Mary Marovich; Surat Jongrakthaitae; Siriwat Akapirat; et al. (PLoS Pathogens, 2014)
Mucosal Th17 cells play an important role in maintaining gut epithelium integrity and thus prevent microbial translocation. Chronic HIV infection is characterized by mucosal Th17 cell depletion, microbial translocation and subsequent immune-activation, which remain elevated despite antiretroviral therapy (ART) correlating with increased mortality. However, when Th17 depletion occurs following HIV infection is unknown. We analyzed mucosal Th17 cells in 42 acute HIV infection (AHI) subjects (Fiebig (F) stage I-V) with a median duration of infection of 16 days and the short-term impact of early initiation of ART. Th17 cells were defined as IL-17+ CD4+ T cells and their function was assessed by the co-expression of IL-22, IL-2 and IFNγ. While intact during FI/II, depletion of mucosal Th17 cell numbers and function was observed during FIII correlating with local and systemic markers of immune-activation. ART initiated at FI/II prevented loss of Th17 cell numbers and function, while initiation at FIII restored Th17 cell numbers but not their polyfunctionality. Furthermore, early initiation of ART in FI/II fully reversed the initially observed mucosal and systemic immune-activation. In contrast, patients treated later during AHI maintained elevated mucosal and systemic CD8+ T-cell activation post initiation of ART. These data support a loss of Th17 cells at early stages of acute HIV infection, and highlight that studies of ART initiation during early AHI should be further explored to assess the underlying mechanism of mucosal Th17 function preservation.